(untitled) (Research, Society and Development, 2021)
The aim of this study was to estimate the prevalence of use of licit and illicit drugs and verify the behavioral profile among truck drivers. A total of 697 truck drivers were interviewed at a gas station on BR-153, between from February 2014 to February 2015. The questionnaire ASSIST was applied to screening the use of alcoholic beverages, tobacco and illicit drugs. Sociodemographic information and professional were also collected. Urine samples were screened for licit and illicit drugs. All of truckers were male, median age of 42 years, most of them married and low scholarity. 47% related moderate or high consumption of alcohol and tobacco and need a brief intervention. 21% use of cocaine, cannabinoids, amphetamine, hypnotics/sedatives, opioids, inhalants and need specialist treatment. From the 697 participants, 94% provided urine samples. 10,5% were positive for drugs. 5,2% were positive for cocaine, 2,6% for cannabinoids, 2,0% for amphetamine, 0,4% for benzodiazepines, 0,3% positive for methamphetamines and 1,4% for combined use of two drugs. Young and single truckers use tobacco, cannabis and amphetamines and need to receive brief intervention for these drugs. Truck drivers in the northern region of low education, require specialized treatment for tobacco. Truck drivers make high use of tobacco, alcohol, cocaine and other ilicit drugs. Measures are needed to improve quality of life to the drivers, as well as to prevent and treat individuals who use licit and illicit drugs in order to reduce engagement with traffic accidents.